Hemólisis aguda post implante de Paraguas de Rashklind en Ductus Arterioso Persistente. Tratamiento Quirúrgico. - CUSTODIO LÓPEZ, Jesús Jacinto (2013)
We report a case of an acute mechanical haemolisis in a woman of 50 years old that ocurred after a percutaneous closure of a patent ductus arteriosus by a Rashkind double umbrella prosthesis.Surgical removal of the device using Cardiopulmonary bypass and ligation of the duct were required before haemolisis was abolished.